Scapular Bronchogenic Cyst in a Girl Presenting as Recurrent Cellulitis: A Case Report and Review of the Literature - Zuhaib M. Mir; Ami Wang; Andrea Winthrop; Mila Kolar (Case Reports in Pediatrics)
Bronchogenic cysts are rare, congenital cysts originating from respiratory epithelium and typically found within the chest. Cutaneous bronchogenic cysts are exceedingly uncommon, with only 19 reported cases in the scapular region and almost exclusively occurring in male patients. Herein, we present the case of a female patient with recurrent cellulitis secondary to a bronchogenic cyst, which was diagnosed after surgical excision. We also provide a review of the literature to consolidate the current understanding of cutaneous scapular bronchogenic cysts. To our knowledge, this is the first such case reported from Canada.